2011
DOI: 10.1055/s-0031-1296444
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acarbose on Blood Glucose and Breath Hydrogen after Carbohydrate Load with Sucrose or Starch

Abstract: A monocentric, open, randomised, single-dose, six-period crossover trial was carried out in healthy volunteers under fasting conditions to establish the most appropriate study design for a pivotal bioequivalence trial with acarbose (CAS 56180-94-0) regarding a) dosage of the drug, b) type of carbohydrate load, c) type of primary endpoint, and d) sample size. 50 g sucrose or 50 g starch were used as carbohydrate load. Acarbose was administered in doses of 50 and 200 mg. Blood glucose and breath hydrogen were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
(3 reference statements)
0
8
1
Order By: Relevance
“…So administration of sucrose was recommended to provide a better baseline measure of α -glucosidase activity. Koytchev et al [ 40 ] administration of sucrose is more suitable than eating a meal since it produces a more reproducible change in serum glucose concentration. Studies on low dose SCE were not reported in healthy people nor in disease condition.…”
Section: Discussionmentioning
confidence: 99%
“…So administration of sucrose was recommended to provide a better baseline measure of α -glucosidase activity. Koytchev et al [ 40 ] administration of sucrose is more suitable than eating a meal since it produces a more reproducible change in serum glucose concentration. Studies on low dose SCE were not reported in healthy people nor in disease condition.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the FDA guidelines for demonstrating acarbose BE published in 2009, administration of sucrose was recommended to provide a better baseline measure of α-glucosidase activity. As found by Koytchev et al (2009), administration of sucrose is more suitable than eating a meal since it produces a more reproducible change in serum glucose concentration (4).…”
Section: Fda Guidelinesmentioning
confidence: 90%
“…Additionally, it suggested increased incidence of gastrointestinal symptoms with sugar rich soft drink consumption. 168 Thus, rational use, slow titration from low to medium dose, focused patient education and good dietary advice may help ameliorate the gastrointestinal adverse effects associated with acarbose.…”
Section: Side Effectsmentioning
confidence: 99%